2010
DOI: 10.1186/1546-0096-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to secondary prophylaxis and disease recurrence in 536 Brazilian children with rheumatic fever

Abstract: BackgroundMore than 15 million people worldwide have rheumatic fever (RF) and rheumatic heart disease due to RF. Secondary prophylaxis is a critical cost-effective intervention for preventing morbidity and mortality related to RF. Ensuring adequate adherence to secondary prophylaxis for RF is a challenging task. This study aimed to describe the rates of recurrent episodes of RF, quantify adherence to secondary prophylaxis, and examine the effects of medication adherence to the rates of RF in a cohort of Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 23 publications
1
41
2
Order By: Relevance
“…ARF/RHD patients not receiving adequate secondary prophylaxis are at risk of avoidable and progressive heart damage. Suboptimal delivery of secondary antibiotic prophylaxis has been highlighted in numerous countries including Australia, 9 Egypt, 10 Taiwan, 11 Brazil, 12 and South Africa. 13 It has been suggested that the underutilization of LAB may be because of the longevity and inconvenience of treatment (up to 20 years of LAB), the pain of injections, poor community engagement, inadequate patient education, cost and distance from health centres.…”
mentioning
confidence: 99%
“…ARF/RHD patients not receiving adequate secondary prophylaxis are at risk of avoidable and progressive heart damage. Suboptimal delivery of secondary antibiotic prophylaxis has been highlighted in numerous countries including Australia, 9 Egypt, 10 Taiwan, 11 Brazil, 12 and South Africa. 13 It has been suggested that the underutilization of LAB may be because of the longevity and inconvenience of treatment (up to 20 years of LAB), the pain of injections, poor community engagement, inadequate patient education, cost and distance from health centres.…”
mentioning
confidence: 99%
“…Suboptimal use of inexpensive interventions such as secondary penicillin prophylaxis and oral anticoagulation is well recognized, 9,10 and contemporary data are needed to 8 document the impact of their underuse on important clinical outcomes. In addition, there is limited information on the determinants of disease progression and on clinical outcomes in contemporary patients with RHD living in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…[22,30] Secondary prophylaxis has been shown to be effective only when there is a high level of compliance, with an increased risk of recurrence and more severe RHD among patients defaulting treatment. [31][32][33] While the majority (96.2%) of children previously diagnosed with ARF/RHD were on penicillin prophylaxis at presentation, only 68.0% reported taking the prophylaxis regularly. This lack of adherence to penicillin prophylaxis has also been reported in a study from 16 developing countries between 1986 and 1990, when adherence was reported to be 63.2%.…”
Section: Discussionmentioning
confidence: 99%